Bat predation by Barn Owls (Tyto alba) in central-eastern Argentina - Massa, Carolina (2015)
We report the predation of bats by Barn owls (Tyto alba) in Entre Ríos province (~33.2º S-33.7º S), central-eastern Argentina. We studied pellet samples from 87 localities, registering 12 species of bats of two families. The best-represented taxa in the samples were the molossids Tadarida brasiliensis (40.7%), Molossus molossus (8.7%), the vespertilionids Myotis spp. (19.67%) and Eptesicus furinalis (9.2%). Molossops temminckii was documented for the first time in the province. The average weight of bats consumed by Barn Owl ranged from ~4 g (Myotis spp.) to ~68 g (Eumops perotis). In terms of frequency, bats represented between 0.04 and 5.11% of the owl?s diet. Our results, together with literature records, suggest that bats tend to be captured more regularly in tropical to subtropical areas than in temperate to cold ones, and that they represent a minor item in the diet of Barn Owls.